ANALYSIS OF THE POWER DRIVES OF TERRAIN FORKLIFTS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
The main subject of this publication is to provides a description of terrain forklifts, their design and specific features. The main mechanical, hydrodynamic and hydrostatic types of power drives and their application in terrain forklifts are presented herein. This article includes an analysis of the power transmissions drive systems of terrain forklifts. The most important trends in the development of the terrain forklifts have also been presented.